Вплив розосереджених джерел енергії на оптимальний потокорозподіл в електричних мережах - Лежнюк, Петро Дем'янович; Гунько, Ірина Олександрівна (НТУ "ХПІ", 2016)
В роботі розглядається питання зменшення втрат активної потужності в локальних електричних системах, в яких експлуатуються різнотипні розосереджені джерела енергії, серед яких сонячні електростанції та гідроелектростанції. В статті наведена комп’ютерна модель режиму локальної електричної системи, яка дозволяє визначити місце точок потокорозділу та розрахувати втрати потужності при розімкненні схеми в відповідних вузлах. Показано, що в умовах використання декількох розосереджених джерел енергії в локальній електричній системі оптимальну за втратами енергії точку потокорозділу (з декількох можливих точок потокорозділу) вибирають за найменшою вузловою напругою. Регулювання потужності енерування малої гідроелектростанції впливає на зміну точки потокорозділу в локальній електричній системі і, відповідно,на втрати електроенергії в ній.

Intensive implementing distributed generation sources from alternative energy sources leads to a situation where one feeder can connect several different types of distributed energy sources, including solar power plant and small hydropower plant. The system consists of distributed generation small-capacity power plants scattered through out the energy system. They supply electricity to consumers in the near and in the case of excess energy can transfer its network centralized power. This paper discusses the reduction of active power losses in the local electrical systems that operate different types dispersed energy sources. The main goal is to develop a methodology for determining the point of power flow section the local electrical system of dispersed generation sources and develop a method for choosing the optimal place network disconnection criterion of active power losses. The article shows the computer model regime for local electricity system that allows to determined the place point of power flow section and calculated the power loss at section schemes in the respective nodes. The choice of multi sections is difficult optimization problems. It is proved that in the use of multiple distributed sources of energy in the local electrical system for optimum energy losses point of power flow section (several possible points of power flow section) is selected at the lower junction voltage. Regulation of power generated by small hydroelectric power plant affects the change point of power flow section local electric networks and reduces the active power losses in the local electrical system.
The impact of distributed power sources to the best of flow in electrical networks
Keywords: сонячні електростанції; точка потокорозділу; локальні електричні системи; гідроелектростанції; втрати активної потужності; distribution power sources; solar power plant; local electrical systems; active power losses